Marketing Strategy of Small Business Management in Improving Business Profit - Wasfika, Hesti; Aswat, Ibnu; Karpriana, Angga Permadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Marketing strategies such as price, location, and promotion are crucial in optimizing revenue. This research aims to identify effective marketing strategies to increase the profits of Lavender Laundry by using SWOT analysis. A qualitative research approach with a case study method is used, focusing on Lavender Laundry as a single research object. Data collection is carried out through interviews with the owner, observations of laundry operations, and secondary data from relevant documents. This approach provides insights into the challenges faced, such as competition from similar businesses, and the strategies employed to maximize opportunities. The business plans to expand by partnering with local accommodations and opening a new branch in a central location to improve accessibility. Despite the threat of competition, strategic collaborations and expansion plans show Lavender Laundry’s efforts to maintain and grow its presence in the market. The business is profitable, with fluctuating but stable revenues, indicating effective marketing strategies and operational success.